THE IMPLICATIONS OF FREE TRADE AREA FOR POVERTY, HOUSEHOLD WELFARE AND ECONOMIC DEVELOMENT IN NIGERIA - Idris, Abubakar; Thomas , Abaukaka; Muhammadkabir , O Momoh (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2021)
ReducingPoverty and increasing household welfare remain among the major socio-economic problems confronting most developing countries especially sub-Sahara Africans which demand policy measures to tackle it. The relevance for free trade area as one of the economic policies to promote welfare and reduce poverty among nations is gaining momentum globally especially the continent of Africa. Given the paucity of studies on this area, the study was undertaken as a framework to determine what the implications of free trade areas will be within the African continent. To achieve this, a fully modified least squares (FMOLS) regression technique was employed to estimate time series data drawn from central bank statistical bulletin spanning the period 1991 to 2017. Econometric view statistical software version 7 was used. Study revealed that free trade scenarios contributed positively to the welfare of individual as well leading to reduction of unemployment. It is recommended based on findings, that policy makers should focus more on policies that will promote foreign direct investment, export contributions to growth and simplification of trade regulations so as to further improve on the positive gains of free trade area on the households’ welfare, and poverty in Nigeria